2013
DOI: 10.2172/1220277
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Environmental Quality Benefits of Apartment Energy Retrofits

Abstract: Sixteen apartments serving low-income populations in three buildings were retrofit with the goal of simultaneously reducing energy consumption and improving indoor environmental quality (IEQ). Retrofit measures varied among apartments and included, among others, envelope sealing, installation of continuous mechanical ventilation systems, upgrading bathroom fans and range hoods, attic insulation, replacement of heating and cooling systems, and adding wall-mounted particle air cleaners. IEQ parameters were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 6 publications
1
51
0
Order By: Relevance
“…It has been suggested that multilevel interventions are necessary to properly assess and improve the indoor environment of low-income residents (Brugge et al, 2003; Sandel et al, 2004). Previous studies have emphasized the potential for IAQ improvements through retrofit measures that also make houses more energy-efficient (Noris et al, 2013). However, even with lower emission materials, tighter homes still have the potential of poorer IAQ due to reduced air exchange.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that multilevel interventions are necessary to properly assess and improve the indoor environment of low-income residents (Brugge et al, 2003; Sandel et al, 2004). Previous studies have emphasized the potential for IAQ improvements through retrofit measures that also make houses more energy-efficient (Noris et al, 2013). However, even with lower emission materials, tighter homes still have the potential of poorer IAQ due to reduced air exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure assessments comparing conventional buildings to green buildings show reductions in several key pollutants associated with symptom reports including particles, nitrogen dioxide, volatile organic compounds, and allergens [1113]. However, the IEQ improvements did not extend to CO 2 or air exchange rate, demonstrating the influence of energy efficiency on green building operation and design.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Past research show large variability in indoor air quality between units (Noris et al 2013) following retrofit measures that included adding a wall-mounted air cleaner to each unit. Sampling in different units is likely needed in order to properly characterize how the between-unit airflow may impact filtration system performance.…”
Section: Discussionmentioning
confidence: 99%